2021
DOI: 10.3390/en14051348
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of Asymmetric Mid-Range Wireless Power Transfer System with Metamaterials

Abstract: In a wireless power transfer (WPT) system, the power transfer efficiency (PTE) decreases sharply with the increase in transfer distance. Metamaterials (MMs) have shown great potential to enhance PTE in mid-range WPT systems. In this paper, we propose two MM slabs of a 3 × 3 array to enhance the magnetic coupling. The MM unit cell was designed by using square spiral patterns on a thin printed circuit board (PCB). Moreover, the asymmetric four-coil WPT system was designed and built based on the practical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, a concern is that some previously reported MTMs have had bulky and volumetric structures such as 3D and thick. printed circuit-board-based structures, reducing the practicality of MTM slabs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. If additional volumetric MTM slabs were permanently located in the power-transfer path, it would greatly limit the usage of the space, diminishing the usefulness of the WPT system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a concern is that some previously reported MTMs have had bulky and volumetric structures such as 3D and thick. printed circuit-board-based structures, reducing the practicality of MTM slabs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. If additional volumetric MTM slabs were permanently located in the power-transfer path, it would greatly limit the usage of the space, diminishing the usefulness of the WPT system.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for the efficient utilization of space, modern commercial electronic devices change their form factors and are deformed, folded, and rolled, e.g., foldable, flipped phones, and rollable televisions, without degrading the performance of the electronic devices while promoting their portability. In this respect, previously demonstrated WPT systems utilizing MTMs have not been compliant with this trend, as their structures have been thick, huge, or rigid [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] for modern electronic devices. In our previous work [ 14 ], a rollable MTM screen for a high-efficiency WPT system was designed at 4.5 MHz, where only the MTM screen was rollable, while the source, Tx, Rx, and load coils were made of non-planar and non-rollable rigid structures.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from one MTM slab, it is revealed that two MTM slabs are more advantageous for efficient power transfer. In Zeng et al, 31 a midrange distance WPT system with two MTM slabs of a 3 × 3 array is proposed to enhance magnetic coupling between coils. The study shows that the power transfer efficiency of the proposed system is higher than that of WPT with one MTM slab.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials or metasurfaces are widely used to improve the WPT efficiency of their unique electromagnetic properties [ 14 , 15 , 16 ], which is not seen in natural materials, such as the zero refraction metamaterials, the negative refractive index (NRI) and negative permeability (MNG) metamaterials [ 17 , 18 , 19 , 20 , 21 , 22 ]. The authors in [ 14 ] propose two metamaterial slabs of a 3 × 3 array to enhance the magnetic coupling. The influence of electromagnetic metamaterials on the WPT system under the conditions of lateral misalignment and angular offset was investigated in [ 15 ].…”
Section: Introductionmentioning
confidence: 99%